18F-FDG PET/CT in Primary Intraosseous Squamous Cell Carcinoma. (5th July 2022) - Lin, Shuai; Fang, Na; Zhang, Jing; Wang, Yan-Li
Abstract: Primary intraosseous squamous cell carcinoma is a highly malignant but rare tumor within jaws. We reported the 18 F-FDG PET/CT findings of primary intraosseous squamous cell carcinoma of the mandible in a 42-year-old man. 18 F-FDG PET/CT identified a cystic lesion in the mandible with irregular annular uptake of 18 F-FDG, which has been confirmed as primary intraosseous squamous cell carcinoma pathologically.